The Condition of Special Library Services for People with Disability in âChildren with Disability Foundationâ (YPAC) Surabaya - Mutia, Fitri (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2015)
The Research about library services for people with disabilities is still found rarely, therefore, in this research case, the researcher try to discuss the title in order to enrich the librarianship scientific. This research uses a quantitative approach with the descriptive type. Some findings of the data presented in this research case is about the collection, type of service, the library manager and the library space of Surabayaâs YPAC. In Surabayaâs YPAC is available only in hard copy collections amounted to approximately 1000-1500 ex, that dominated the collection of fiction (stories/illustrated fables). The condition of most of the collection is very alarming because it was never noticed, classified specifically and many collections are laid out horizontally as high book shelf height exceeds available. YPAC library runs only circulation services manually, and organized by teachers who graduate from educational of school for disabled (SLB). Regarding the library are in good condition and clean, there are 4 and 3 units of rackcollection of tables and chairs, but the air circulation is not good because the ventilation system only comes from a window so that the temperature inside the room pretty hot.